(untitled) (Dhaka University Journal of Pharmaceutical Sciences, 2019)
UV spectrophotometric methods for the determination of pitavastatin calcium in pure and pharmaceutical dosage forms were developed and validated as per ICH guidelines. The standard pitavastatin calcium solutions were scanned between the ranges of 200-400 nm. The maximum absorbance of pitavastatin calcium in DMF (method A), HCl (method B) and NaOH (method C) was recorded at 266 nm. They obeyed Beers law concentration in the range of 10-45 μg/ml (method A), 0.25-2.0 μg/ml (method B) and 0.25-2.0 μg/ml (method C) with correlation coefficients 0.9996, 0.9998 and 0.9998 respectively. Stability study showed high stability of pitavastatin calcium in acidic, alkaline medium and at high temperature, but undergone degradation in oxidative stress condition. The developed methods were validated for linearity, precision, accuracy, LOD, LOQ, ruggedness, robustness and recovery studies. The proposed methods can be successfully used for the routine quality control analysis of pitavastatin calcium in bulk and commercial pharmaceutical formulations. Dhaka Univ. J. Pharm. Sci. 18(2): 159-169, 2019 (December)